Banana-peel-derived magnetic porous carbon as effective adsorbent for the enrichment of six bisphenols from beverage and water samples. (15th May 2022) - Liang, Ming; Hou, Xiangchang; Xian, Yanping; Wu, Yuluan; Hu, Junpeng; Chen, Rongqiao; Wang, Li; Huang, Yufeng; Zhang, Xiaoli
Highlights: Functionalized magnetic porous carbon was prepared from banana peel. Enrichment of 6 BPs from beverage and bottled water was achieved by prepared material. An HPLC-Q Orbitrap HRMS method was developed for detection of 6 BPs. Method with favorable selectivity provided high recovery and high enrichment factor. Abstract: Functionalized magnetic nanoporous carbon derived from banana peel was synthesized through carbonization, porogenesis, carboxylation and magnetization using banana peel and was successfully used as a magnetic solid phase extraction (MSPE) material for the enrichment of six bisphenols (BPs) from beverage and water samples. After the optimization of MSPE process, the enrichment factors of six target analytes were in the range of 74–112 for water samples, and 15–22 for beverage samples. Then, high-performance liquid chromatography–quadrupole-Orbitrap high-resolution mass spectrometry (HPLC–Q Orbitrap-HRMS) was used for the separation and determination of the target analytes. Results showed that the extraction recoveries for 6 BPs were in the range of 71.9–108.4% with an RSD of 2.5–7.5% ( n  = 6). These results demonstrated that the as-prepared material could efficiently enrich some aromatic compounds and the proposed method is reliable and robust for the determination of BPs in water and beverage samples.